Identifikasi Karakteristik Seni Lukis Flora Dan Fauna Pengosekan Pada Seni Kerajinan Batu Padas Di Desa Singapadu - Ni Putu Laras Purnamasari (Mudra Jurnal Seni Budaya, 2022)
Pengosekan painting was once a favorite among tourists in theera of the 1980s. Pengosekan paintings are widely used as an aesthetic element of the interior of hotels, restaurants, office spaces, hospital rooms, and are exported abroad as souvenir products. Along with the heyday of Pengosekan painting, representations of this painting were found in several handicrafts. One of the handicraft arts that represents Pengosekan painting is the art of stone craft that has developed in Singapadu Village, Sukawati District, Gianyar Regency, Bali. There are similarities in terms of themes and the creation of solid stone craft objects with Pengosekan painting. This research specifically identifies the characteristics of the Pengosekan painting which is represented in the art of rock craft in Singapadu Village, as well as its influencing factors.This research is a qualitative research, using representation theory as analysis tools. The results showed that there was a representation of Pengosekan painting in the arts, which was seen in terms of the theme and character of the visual object. The representation that occurs is influenced by the artist's motivation to create innovation, as well as being influenced by the developing market at that time.